2005
DOI: 10.1055/s-2004-817878
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polar 810 s and an Ambulatory ECG System for RR Interval Measurement During Progressive Exercise

Abstract: Ambulatory heart rate monitors and clinical electrocardiographic (ECG) devices are capable of measuring the length of consecutive cardiac periods (RR intervals). The aim of the study was to assess the agreement between the Polar 810s heart rate monitor (Polar) and the Reynolds digital ambulatory ECG using Pathfinder software version 8.4 (Reynolds v8.4) during cycle ergometry. For this purpose, eight subjects completed incremental cycling exercise that began at 60 W and increased by 30 W each 2-minute period un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
10
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 10 publications
11
136
10
11
Order By: Relevance
“…In order to facilitate HRV analysis, a wide variety of equipment and software programs have been developed, such as PowerLab (ADInstruments, Australia) (3) and the Reynolds Pathfinder program (Reynolds Medical Limited, United Kingdom) (10), which measure HRV by means of an ECG signal. However, they present disadvantages such as difficulty of access and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate HRV analysis, a wide variety of equipment and software programs have been developed, such as PowerLab (ADInstruments, Australia) (3) and the Reynolds Pathfinder program (Reynolds Medical Limited, United Kingdom) (10), which measure HRV by means of an ECG signal. However, they present disadvantages such as difficulty of access and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Se debe resaltar que, en el presente estudio, se utilizó el registro de los intervalos RR en el transiente inicial de ejercicio con inicio repentino. A pesar de ello, se encuentran valores semejantes a los reportados por Kingsley et al 17 y Gamelin et al 21 , que estudiaron la validad del MFC en ejercicio progresivo y en reposo. Los límites de concordancia aquí encontrados fueron menores que los reportados en los estudios ya citados, tal vez porque, en este estudio, se utilizaron en la comparación solamente los intervalos RR usados en la identificación del IVC y no las series completas (> 5 min), usualmente utilizadas.…”
Section: Discussionunclassified
“…Así, Nunan et al 16 encontraron una fuerte correlación cuando compararon el registro y la edición de los intervalos RR entre el ECG convencional y el MFC Polar S810 en condición de reposo, comprobando así la capacidad y aplicabilidad de este instrumento en la adquisición de estos datos. Finalmente, relacionando la validad de estos registros en momentos y maniobras distintos, Kingsley et al 17 no constataron diferencias significativas entre las mediciones del MFC Polar S810 y el ECG para todas las intensidades de ejercicio probadas.…”
unclassified
“…With the fast improving technologies, it is expected that these devices will improve considerably in the next few years. Polar™ equipment is, according to validating studies in humans (e.g., Macfarlane et al, 1989;Thivierge and Leger, 1989;Kingsley et al, 2005;Gamelin et al, 2006), among the most accurate available on the market. Significant problems with some Polar heart rate monitors have been reported (see Gorecka-Bruzda et al, 2012;Suwala et al, 2012), so it is suggested that each device should at least be cross-validated against a second device.…”
Section: A What Endpoints To Measurementioning
confidence: 99%